Judicial Review and Its Role in Detecting Mistakes in order to Reduce the Phenomenon of Fraud and Manipulation in the Supply Chain Financing of Public Corporations - Mohammed Jaber Kadhim; Hayder Sabri Sarhan; Azhar Ghailn Marhoon (International Journal of Supply Chain Management, 2019)
This paper examines the types of fraud in the financial affairs of public corporations and the way they deal with them and ultimately the right to judicial review. The results of the investigations showed that after proving any crime and issuing a lower court judgment, there is a right for the offender to seek authority from the authorities in order to obtain a reduction in the punishment. The multiplicity of judicial procedures is a mechanism and tool for correcting a mistake or probable judicial error. In fact, if at the initial stage or appeal (research or material revision) occurred due to a mistake in the judicial decision to violate the right or to violate it, in the later stages, by modifying the decision, provide rights and remedy and possible compensation. By reducing such mistakes in the judicial review process, it has been possible to detect fraudulent fraud in corporate supply chain financing and close the ways of circumventing the law to managers and auditors.